Hume on Church Establishments, Secular Politics and History (Diametros, 2018)
In the third volume of the History of England, David Hume considers the political ramifications of the Protestant reformation with a “Digression concerning the ecclesiastical state.” He advocates the establishment of a state church, believing it will dampen religious “enthusiasm” in the polity. Unlike later secularization theorists, Hume assumes an intractable basis for religion in the human passions. Tensions in Hume’s “cooptation” strategy are evident from Adam Smith’s famous attack upon it in section five of The Wealth of Nations, and in Hume’s own treatment of seventeenth century independency in the fifth volume of the History. Smith argues that public competition among sects facilitates political moderation. In History V Hume stresses the positive role of enthusiasm in fostering civil liberty. This article traces Hume’s indecision to his “external” mode of moral and historical analysis, arguing that a secular policy on religion cannot proceed fruitfully without engaging the theological particulars of the religions at issue.